(untitled) (Web of Teachers: Inderscience Research, 2026)
Intercultural dialogue plays a crucial role in promoting mutual understanding, peaceful coexistence, and social cohesion in increasingly diverse societies. However, dialogue across cultures does not occur in a neutral or equal space. Gender inequality and broader forms of social inequality often shape who participates, whose voices are heard, and whose perspectives are legitimized. This article examines key issues of gender equality and social equality within the context of intercultural dialogue. Drawing on human rights frameworks and the concept of intersectionality, the study analyzes structural barriers, cultural stereotypes, and institutional inequalities that limit inclusive participation. The article argues that gender equality and social justice must be treated as foundational principles—not optional outcomes—of intercultural dialogue. Finally, it proposes policy- and education-oriented strategies to promote inclusive, equitable, and rights-based intercultural engagement.